Indications and complications of paediatric tracheostomies at a tertiary care centre in rural Haryana: a retrospective study - Yadav, Mayank; Yadav, Garima; Monga, Jasdeep; Hussain, Raj Tajamul; Naik, Sulabha M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The indications for paediatric tracheostomies have had a significant change world over during last few decades. Emergency management of paediatric airway by tracheostomy has its own share of complications which need fair amount of expertise to manage. Methods: We carried out a retrospective study at a tertiary care centre in rural area of Haryana and analysed the available data of last 5 years (2017-2021) for determining various indications of paediatric tracheostomies and complications encountered during or after the surgery. Results: The study included 65 paediatric patients (<14 years of age) who underwent tracheostomy at our tertiary care institute between January 2017 and December 2021. Out of them 38 (60.3%) were males, 35 (55.17%) patients were in 0-5 years age group. Most frequent indication for paediatric tracheostomy turned out to be upper airway obstruction due to a vaccine preventable disease diphtheria (n=56, i.e., 86.15%), other less common causes were need of prolonged ventilation, subglottic stenosis, congenital airway anomalies, retropharyngeal abscess, laryngeal papilloma. Complications were observed in 30 cases (46.15%). Mortality in tracheostomized children was nearly 29.2%, which was mainly attributed to the underlying cause which turned out to be diphtheria in most of the cases. Conclusions: High number of paediatric tracheostomies and sheer presence of diphtheria in this rural area of Haryana suggests that there is dire need of proper immunisation coverage and an active participation at community level.